2015
DOI: 10.1128/jcm.01062-15
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Core Mutations Associated with False-Negative Serological Results for Genotype 3a Core Antigen

Abstract: Genetic characterization of the genotype 3a (GT3a) hepatitis C virus (HCV) core region from HCV core antigen (HCVcAg)-negative/RNA-positive cases and HCVcAg-positive/RNA-positive controls identified significant associations between the substitutions A48T and T49A/P and failure to detect HCVcAg (P < 0.05). Polymorphisms at residues 48 and 49 in the core protein are present across all major epidemic and endemic GTs. These findings have implications for HCV diagnosis, particularly in low-income regions in which G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 17 publications
3
23
0
2
Order By: Relevance
“…A48T mutation is present in all genotypes (range: 0.35-6.70%). T49A mutation is present in all genotypes (range: 0.1-4.50%), T49P is present in GT2 (as well as Gt1a, GT1b and GT4, range: 0.4-15.7%) [19]. Those mutations were detected in the subsequent time-points (week 4, SVR12 and FU1).…”
Section: Hcvcag Sequencing To Identify Hcv Core Mutations Associated mentioning
confidence: 79%
See 2 more Smart Citations
“…A48T mutation is present in all genotypes (range: 0.35-6.70%). T49A mutation is present in all genotypes (range: 0.1-4.50%), T49P is present in GT2 (as well as Gt1a, GT1b and GT4, range: 0.4-15.7%) [19]. Those mutations were detected in the subsequent time-points (week 4, SVR12 and FU1).…”
Section: Hcvcag Sequencing To Identify Hcv Core Mutations Associated mentioning
confidence: 79%
“…For screening HCV in low prevalence setting, a three step algorithm with HCV antibody, followed by HCVcAg (for HCV ab reactive result) and finally HCV RNA test (for HCVcAg non-reactive result) would be cost effective in achieving 100% detection of active viraemia as previously described [37]. This study also identified six genotype 3 participants for whom the HCVcAg assay was consistently negative and HCV RNA levels quantifiable, five of whom could be attributable to amino acids substitutions identified in Core region previously showed to affect HCVcAg serological result [19]. Little data on the prevalence of those mutations are known in the general population and more studies are required to assess the impact of false negative HCV detection due to core antigen mutations on all genotypes.…”
Section: Journal Of Clinical Virology 92 (2017) 32-38mentioning
confidence: 80%
See 1 more Smart Citation
“…Ранее было показано влияние субтипов ВГС на соот-ношение вирусной РНК и core-антигена [22,23]. В на-стоящем исследовании это было изучено для доминирую-щих субтипов вируса у детей с ХГС (табл.…”
Section: результаты и их обсуждениеunclassified
“…Самое высокое соотношение установлено для субти-па 3а, что подтверждается данными, полученными при анализе образцов взрослых пациентов [10,22,23].…”
Section: результаты и их обсуждениеunclassified